Performance of CT Scan in diagnosis of Sinonasal mass (Bangladesh Journal of Otorhinolaryngology, 2019)
Objective: To establish CT scan as a sensitive modality in the diagnosis of sinonasal mass by correlating with the findings of histopathological examinationMethods: This cross sectional study was conducted in Dhaka Medical College Hospital (DMCH) from 01/07/2013 to 30/06/2014. A total of 32 cases were studied.Results: In this study male and female ratio was 1.4:1. So, the incidence of sinonasal mass slightly higher in male (59.3%) compared to the female (40.6%). Incidence of malignant tumour was found more in age group above 60 years. Out of 32 patients, 6 patients (18.7%) were diagnosed histopathologically as infective, 7 patients (21.8%) were benign and 19 patients (59%) had malignant sinonasal mass.Conclusion: Computed tomography (CT) scan examination of the sinonasal mass correlate well in most of the cases with histopathological results. It is therefore can be concluded that CT examination of nose and paranasal sinuses is a useful modality in the evaluation of sinonasal mass. Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 149-155